GASTROINTESTINAL DIGESTION OF KAHAI PROTEIN CONCENTRATE (CARYODENDRON ORINOCENSE KARST) - J, Greffa; A, Barrionuevo; E, Vilcacundo; W, Carrillo (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was to obtain kahai protein concentrate from Caryodendron orinocense karst cultivated in the region Amazonia of Ecuador and characterizes its gastric and duodenal hydrolysates using the sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) electrophoresis method and the reversed-phase ultra-high-performance liquid chromatography (RP-UHPLC) method. Methods: Kahai seeds (C. orinocense karst) were utilized to obtain kahai protein concentrate at pH 5.0 using the isoelectric precipitation method and then subject to gastric hydrolysis with pepsin enzyme (2000 U/mg of protein) at pH 1.2, pH 2.0, and pH 3.2 at 37Â°C for 2 h with agitation in simulated gastric fluids and then to duodenal hydrolysis with pancreatin (mix enzymes) at pH 7.0 at 37Â°C for 3 h with agitation in simulated intestinal fluid. Gastric and duodenal hydrolysates from kahai were characterized using the SDS-PAGE electrophoresis method and the RP-UHPLC chromatography method. Results: Proteins obtained from kahai (C. orinocense karst) were hydrolyzed with pepsin, only one protein with molecular weight of 100 kDa presented resistance to hydrolysis with pepsin at all pHs assayed. All proteins from kahai protein concentrate were totally hydrolyzed with pancreatin in in vitro conditions. Conclusion: This study suggests that kahai protein concentrates have a high grade of digestibility in vitro when using the gastroduodenal model of digestion. Kahai protein can be a good source of alternative vegetal proteins to be consumed by animals and humans.